Influence of thyroidectomy on postoperative serum calcium level regarding serum vitamin D status. A prospective study - Gholamali Godazandeh; Zahra Kashi; Farnaz Godazandeh; Pouya Tayebi; Ali Bijani (Babol University of Medical Sciences, 2015)
Background: Hypocalcemia is a well-recognized complication after total thyroidectomy. Hypovitaminosis D may have additional effect in the development of hypocalcemia. This study aimed to determine the effect of total thyroidectomy on postoperative serum calcium in patients with and without hypovitaminosis D. Methods: This prospective study was performed on patients who underwent total thyroidectomy from 2011 to 2014 in Imam Khomeini General Hospital of Mazandaran University of Medical Sciences. Serum calcium and vitamin D values were recorded before and after surgery. The patients were classified according to serum vitamin D concentrations as less 10 ng/ml (vitamin D deficiency) or higher (control group). The mean values of postoperative calcium level for each class of serum vitamin D were determined and compared. Hypocalcemia was defined as a postoperative calcium level <8 mg/dl. Results: 125 patients due to thyroid disease underwent total thyroidectomy. The incidence of symptomatic and asymptomatic hypocalcemia after surgery was 12% (n=15) and 3.2% (n=4) respectively. 82 (65.6%) patients had vitamin D deficiency and 43 (34.4%) patients had sufficient vitamin D level. There was not any significant difference in calcium level (8.67±0.58 mg/dl vs. 8.70±0.59 mg/dl) between two vitamin D studied groups after thyroid surgery (p>0.05). Conclusion: The findings of this study indicated that vitamin D deficiency had no significant effect on post-thyroidectomy serum calcium level.